Solar engineering of thermal processes, photovoltaics and wind - Duffie, John A. (Wiley, 2020)
"The updated Fifth Edition of Solar Engineering of Thermal Processes, Photovoltaics and Wind contains the fundamentals of solar energy and explains how we get energy from the sun. The authors--noted experts on the topic--provide an introduction to the technologies that harvest, store, and deliver solar energy, such as photovoltaics, solar heaters, and cells. The book also explores the applications of solar technologies and shows how they are applied in various sectors of the marketplace. The revised Fifth Edition offers guidance for using two key engineering software applications, Engineering Equation Solver (EES) and System Advisor Model (SAM). These applications aid in solving complex equations quickly and help with performing long-term or annual simulations. The new edition includes all-new examples, performance data, and photos of current solar energy applications. In addition, the chapter on concentrating solar power is updated and expanded. The practice problems in the Appendix are also updated, and instructors have access to an updated print Solutions Manual."--